Analisis keterampilan berpikir kritis dalam pemecahan masalah geometri ditinjau dari efikasi diri peserta didik kelas V sekolah dasar - Chandra Ramdhan Shilton; Riyadi Riyadi; Roy Ardiansyah (Didaktika Dwija Indria, 2025)
This study aims to describe the critical thinking skills in solving geometry problems among fifth-grade elementary school students with high, moderate, and low self-efficacy at SDIT BIT Surakarta. The research employs a qualitative approach. The data sources consist of six fifth-grade students from SDIT BIT Surakarta. Purposive sampling was used as the sampling technique. The data collection methods include task-based interviews and questionnaires. The results indicate that students with high self-efficacy can effectively meet all four indicators of critical thinking, namely interpretation, analysis, evaluation, and inference. Students with moderate self-efficacy are able to adequately meet these four indicators. Meanwhile, students with low self-efficacy only meet two indicators: interpretation and analysis. Therefore, the higher the self-efficacy possessed by students, the greater their critical thinking ability in solving geometry problems.